A Risk Analysis Affecting Project Implementation with Contract Values Below 80% of the Owner's Estimated Price - Istijono, Bambang; Ophiyandri, Taufika; Gustia, Siti Rahmi (Jurnal Talenta Sipil, 2025)
The number of bids is less than 80% of the HPS, meaning that the work offered will be carried out at a cost of less than 80% of the estimated cost of the person in charge of the work. In the 2020 period the average percentage of contract value with an offer value of < 80% HPS at Agency x tends to increase significantly by 80% compared to the 2019 period. If the HPS preparation is assumed to have been carried out in accordance with expertise and supported by accountable data. Therefore, the implementation of a contract with a bid value below 80% HPS has a greater possibility of risk in the field compared to a contract value with an offer value above 80% HPS. The method used in carrying out this research is the descriptive method, namely through direct interviews with the Commitment Making Officer (PPK) at agency x to obtain information about the purpose of this research, namely, knowing what risks arise, the causes of risks, and what anticipatory steps are taken. to reduce risk. From the results of data processing after being validated with sources, the risks that arise are: contract extension, contract termination, reduced construction age, disputes, and bad news from local media caused by the bid value which is considered unreasonable. Steps taken by the owner as the owner of the project to reduce risk are Terminating the contract for projects found to be deviant according to applicable regulations and tightening supervision to maintain the quality of work.